Mission profile-based reliability design and real-time life consumption estimation in power electronics - Mussallam, Mahera; Yin, Chunyan; Bailey, Christopher; Johnson, Christopher Mark (Institute of Electrical and Electronics Engineers, 2014)
Power electronics are efficient for conversion and conditioning of the electrical energy through a wide range of applications. Proper life consumption estimation methods applied for power electronics that can operate in real-time under in-service mission profile conditions will not only provide an effective assessment of the products life expectancy but also they can deliver reliability design information. This is important to aid in manufacturing and thus help in reducing costs and maximizing through-life availability. In this paper, a mission profile based approach for real-time life consumption estimation which can be used for reliability design of power electronics is presented. The paper presents the use of electro-thermal models coupled with physics-of-failure analysis by means of real-time counting algorithm to provide accurate life consumption estimations for power modules operating under in-service conditions. These models, when driven by the actual mission profiles, can be utilized to provide advanced warning of failures and thus deliver information that can be useful to meet particular application requirements for reliability at the design stage. To implement this approach, an example of two case studies using mission profiles of a metro-system and wind-turbines applications are presented.